2019
DOI: 10.9743/jir.2019.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Teacher Experiences in Formal and Informal Co-Operative Learning Groups in a Mathematics Course

Abstract: Co-operative group learning is known to be an effective instructional practice, especially for mathematics. While group work can be incorporated into the classroom in multiple ways, not every group is a co-operative learning community. In the current study, class observations and preservice teacher interviews were used to compare experiences during formal and informal group work. The findings indicate that formal co-operative learning groups, or prolonged interaction with the same group of people, develops a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Group work is a major approach of the (SMC) framework. Previous research reported a positive impact on students' learning, understanding, and motivation (Steinberg &Vinjamuri, 2014;Martin & Towers, 2015;Wegerif et al, 2017), and a positive influence on their self-efficacy (Wyatt, 2010;Mitcham et al, 2012;Chiriac, Rosander, & Frykedal, 2019;Kopparla & Goldsby, 2019), especially when students learn how to work and think together as a group (Wegerif et al, 2017). Chambers and Timlin (2013) provided some detail about…”
Section: Smc: the Conceptual Framework For The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Group work is a major approach of the (SMC) framework. Previous research reported a positive impact on students' learning, understanding, and motivation (Steinberg &Vinjamuri, 2014;Martin & Towers, 2015;Wegerif et al, 2017), and a positive influence on their self-efficacy (Wyatt, 2010;Mitcham et al, 2012;Chiriac, Rosander, & Frykedal, 2019;Kopparla & Goldsby, 2019), especially when students learn how to work and think together as a group (Wegerif et al, 2017). Chambers and Timlin (2013) provided some detail about…”
Section: Smc: the Conceptual Framework For The Studymentioning
confidence: 99%
“…This has also been confirmed by this study, as the following interview extract shows. (Steinberg &Vinjamuri, 2014;Martin & Towers, 2015;Wegerif et al, 2017), but also improved their self-efficacy as well (Chiriac, Rosander, & Frykedal, 2019;Kopparla & Goldsby, 2019). Group work was involved while playing the puzzle sheets, answering the revision notes, and while using different teacher's teaching methodologies.…”
Section: What Features Within the Framework Promoted Improved Students' Self-efficacy Andmentioning
confidence: 99%
“…In a meta-analysis of SEL programs, Durlak et al, (2011) found that students who participated in SEL programs significantly to improve their academic performance, attitude, and behavior. This program also can improve students' knowledge and skills (Fernandez-Rio et al, 2017;Kopparla & Goldsby, 2019;Oberle et al, 2016;Yoder & Nolan, 2018). It further stimulates students' curiosity, responsibility, selfreflection, and development of their competency (Gul & Shehzad, 2012;Hammond et al, 2020;O'Dwyer et al, 2015;Patil et al, 2014;Yoder & Nolan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies on cooperative learning in undergraduate programs have also shown a positive impact (e.g., Dyson & Casey, 2012;Hmelo-Silver et al, 2013;Kopparla & Goldby, 2019). Peters et al (2020) reported that in their study of students working collaboratively in small groups (Team-based Learning) in large-enrolment undergraduate calculus classes, they found "…many positive benefits for students…including ...larger gains on the Calculous Concept Inventory than non-TBL sections" (p. 211).…”
mentioning
confidence: 99%
“…Both notions of cooperative and collaborative groups are aligned with what Tinto (1998), Price (2006), and Rausch and Crawford (2012) refer to as "learning communities" and "communities of inquiry." However, Kopparla and Goldby (2019) quite righty point out "…not every group is a cooperative learning community" (p. 51). And, Johnson et al (as cited in Raush & Crawford, 2012) warned that "simply asking students to work in groups does not necessarily constitute cooperative learning" (p. 318).…”
mentioning
confidence: 99%